Polyvinyl Alcohol/EuBa2Ca2Cu3O9-x Composites: Dielectric and Mechanical Properties - Misirliolu, B. Sungu; Ozdemir, Z. Guven; Aksakal, B.; Salt, Y.; Tirnakci, B.; Denktas, C. (SPRINGER, 2018)
In the present work, the influence of EuBa2Ca2Cu3O9-x (coded as Eu-1223) ceramic additive on the mechanical and dielectric properties of poly(vinyl alcohol) (PVA) polymer were investigated for the first time. PVA/Eu-1223 polymer-ceramic thick film composites were prepared by solution casting method with different ceramic contents varying from 1 to 5%. The surface morphology of the samples were studied with scanning electron microscope revealed that adding higher concentration of Eu-1223 increases the roughness of the surface as well as the fragility of the PVA. Thermogravimetric analyses results revealed that the increasing Eu-1223 additive enhances slightly both the thermal and oxidative stability of the PVA. Furthermore, FTIR analysis of the composite displayed new FTIR transmittance peaks that can be attributed to the formation of a reaction between the PVA polymer chain and the ceramic additive. The mechanical properties in the context of stress-strain curves of the samples unveiled that increasing ceramic doping improves the Young's modulus of PVA films. The impedance and dielectric properties of the samples recorded at room temperature indicated a space charge polarization regardless of the doping concentration. The complex electrical modulus analysis also pointed out a pure conduction process. The Nyquist and phase angle plots defined the grain and grain boundary properties along with the ideal capacitor ability of the composites. Especially, the lower epsilon' and epsilon aEuro(3) values were achieved for the 5% Eu-1223 additive level concentration. This work brings out that 5% Eu-1223 added PVA thick film may be suggested as a low dielectric loss dielectric material for supercapacitor applications.
Keywords: Polymer/ceramic composites; Impedance spectroscopy; Poly(vinyl alcohol); Eu-Ba-Ca-Cu-O; Tensile properties; OXIDE/POLY(VINYL ALCOHOL) COMPOSITE; THERMALLY REDUCED GRAPHENE; NANOCOMPOSITE FILMS; ELECTRICAL-CONDUCTION; STRUCTURAL-PROPERTIES; CAPACITIVE BEHAVIOR; PVA NANOCOMPOSITES; AC-IMPEDANCE; POLYMER; Polymer Science